Development of Fuel/Engine Systems—The Way Forward to Sustainable Transport. (June 2019) - Kalghatgi, Gautam
Abstract: The global demand for transport energy is large, growing, and primarily met by petroleum-derived liquid fuels powering internal combustion engines (ICEs). Moreover, the demand for jet fuel and diesel is projected to grow faster than the demand for gasoline in the future, and is likely to result in low-octane gasoline components becoming more readily available. Significant initiatives with varying motivations are taking place to develop the battery electric vehicle (BEV) and the fuel cell as alternatives to ICE vehicles, and to establish fuels such as biofuels and natural gas as alternatives to conventional liquid fuels. However, each of these alternatives starts from a very low base and faces significant barriers to fast and unrestrained growth; thus, transport—and particularly commercial transport—will continue to be largely powered by ICEs running on petroleum-based liquid fuels for decades to come. Hence, the sustainability of transport in terms of affordability, energy security, and impact on greenhouse gas (GHG) emissions and air quality can only be ensured by improving ICEs. Indeed, ICEs will continue to improve while using current market fuels, through improvements in combustion, control, and after-treatment systems, assisted by partial electrification in the form of hybridization. However, there is even more scope for improvement through the development of fuel/engine systems that can additionally leverage benefits in fuels manufacture and use components that may be readily available. Gasoline compression ignition (GCI), which uses low-octane gasoline in a compression ignition engine, is one such example. GCI would enable diesel-like efficiencies while making it easier to control nitrogen oxides (NO x ) and particulates at a lower cost compared with modern diesel engines. Octane on demand (OOD) also helps to ensure optimum use of available fuel anti-knock quality, and thus improves the overall efficiency of the system.